2009
DOI: 10.1158/1078-0432.ccr-08-3215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3′-Kinase Catalytic Subunit α Gene Amplification Contributes to the Pathogenesis of Mantle Cell Lymphoma

Abstract: Purpose: Activation of phosphatidylinositol 3′-kinase pathway is implicated in the pathogenesis of mantle cell lymphoma (MCL). The genetic change in phosphatidylinositol 3′-kinase catalytic subunit α (PIK3CA) in MCL has not been identified. Experimental Design: Thirty-five primary MCL cases and 2 MCL cell lines (GRANTA-519 and Rec-1) were used to investigate somatic mutation and gene copy number of PIK3-CA. Gene copy number was determined using quantitative real-time PCR and fluorescence in situ hybridization.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 47 publications
3
82
2
Order By: Relevance
“…In keeping with a previous report, 15 we found loss of PTEN expression in 17% of diagnostic (6/35) and 16% of all (22/138) biopsies ( Figure 2C). A higher proportion of tumors exhibiting blastoid morphology had loss of PTEN expression compared to cases with classical histology, but this was not statistically significant (20% vs 15%, P 5 .55 by Fisher's exact test).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In keeping with a previous report, 15 we found loss of PTEN expression in 17% of diagnostic (6/35) and 16% of all (22/138) biopsies ( Figure 2C). A higher proportion of tumors exhibiting blastoid morphology had loss of PTEN expression compared to cases with classical histology, but this was not statistically significant (20% vs 15%, P 5 .55 by Fisher's exact test).…”
Section: Resultssupporting
confidence: 93%
“…3,15 Loss of PTEN expression is another mechanism leading to constitutive activation of the PI3K pathway, and studies in solid tumors have demonstrated a key role for p110b in PTEN-deficient tumors. [16][17][18] Loss of PTEN expression has been described in approximately 15% of MCLs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations